A realistic evaluation of an EP Led Group Consultation Intervention with school staff supporting a looked after child - Austin, Maddi (2018)
The current study evaluates a group consultation intervention, led by an Educational Psychologist (EP) within a Midlands Educational Psychology Service (EPS). The intervention was designed to support school staff in their work with a Looked After Child (LAC) in a UK Primary School setting. A literature review was conducted, and indicated that the current body of research examining group consultation in schools was outcome focused. Group consultation is a complex social programme and therefore the current study aimed to examine the mechanisms and complex psychological processes that address why the intervention may work within the current context. In order to achieve insight into such processes, a realist epistemology was adopted and a Realistic Evaluation (RE) methodology (Pawson & Tilley, 1997) was applied using a case study approach. The RE methodology highlights intricate processes within the intervention through identification of context, mechanism and outcome configurations (CMOCs). Six outcome themes were developed from the literature review and CMOCs within each outcome theme were collated into an Initial Program Theory. The CMOCs were further refined through three evaluation cycles. In evaluation cycle one, data was gathered through an observation of the group process and a Realist Interview (RI) with the facilitating EP. In evaluation cycle two, data was gathered through semi structured interviews with participants and a focus group was conducted in evaluation cycle three, which required participants to categorise final program theories according to perceived importance. Analysis of data was conducted using a thematic analysis that offered a framework to support the refinement and development of CMOCs. Findings suggest that according to participants, the most critical elements of the process were the opportunity to develop a whole group approach to working with the LAC and the skills of the EP facilitator in guiding exploration of the problem. The current research contributes in-depth insight into the critical mechanisms, which supported the perceived outcomes of a group consultation intervention involving the adults working to support a LAC. Limitations and implications for EP practice are considered to conclude the research.